Regime disciplinar diferenciado: análise sistemática em face dos princípios constitucionais penais - Mendes, Ana Paula dos Santos (2009)
This study aims at a systematic approach to the disciplinary system differently, kind of disciplinary penalty imposed on certain prisoners with provisional or final sentencing, which is characterized by its severity and rigor in the face of Constitutional Criminal principles, seeking to verify the compatibility between them. Thus, through the dialectical method, using the definitions of order and system, bringing the vision of the whole law systematically, highlighting the position of human dignity as the main value to inform the Brazilian legal system. It also highlights the importance of principles to inform and interpret the town, emphasizing the principles and Constitutional Criminal task orientation in the relevant legislation. This work shows, even a summary history of the origin of feathers and their purposes, seeking to achieve, the theory adopted in the Brazilian legislation, and demonstrate that the disciplinary action, object of this study, no guard relevance to the objectives pursued in this theory. This summary ends with the social changes that led to differential Disciplinary Scheme, which is Office, then under consideration in its provisions, through doctrinal questions about the effectiveness and applicability of the penalty under study, as well as a comparison of its provisions with the doctrine of "Criminal Law of the Enemy." There is also an analysis of the institute in the face of international human rights treaties to which Brazil is a signatory, demonstrating that they are also part of the town home, and seeking to demonstrate that the Disciplinary Board Differential Neither is related to relevance with the obligations derived these qualifications. By last, given the principles and rules listed homelands, and the values they seek out and also of international obligations regarding the respect for human rights, this study concludes that it is not compatible with the Differentiated Disciplinary Regime Brazilian Penal System, on pain of abandoning the idea of relevance of the standards and vision of law as a systematic and coherent whole